Comprehensive Teaching Strategies: Learning Ecosystems for Twenty-first Century - Regmi, Bhim Nath (Interdisciplinary Issues in Education, 2024)
This paper aims at boosting the effectiveness of teaching ecosystems in addressing the problems of the twenty-first century. It collects facts and required information from primary and secondary sources. Ten informants involved in teaching at AB, BC, CD, DE, and EF campuses; and twenty-five learners from these institutions were taken to discuss teaching strategy and learning satisfaction.  The rapid change in society and technology in the twenty-first century poses unique challenges for human beings. Recognized it as a dynamic process, learning procedure encompasses memory, reasoning, individual mindset, habits, goals, and motivation. The findings of this paper indicate that the positive remarks on preferred teaching strategies, and cooperative learning affect students’ satisfaction. Research on teaching strategies suggests that learning transcends cognitive aspects, extending into social-emotional dimensions and unfolding within environmental and cultural contexts throughout an individual's lifespan. Effective learning and teaching strategies focus on cooperative, resourceful, interactive, and self-regulatory practices. Effective instruction involves a learner-centric approach and concentrates on conceptual understanding, metacognition, assessment, and technology integration, cognitive, social, and emotional development within a supportive environment. The responses gathered from tutors and learners limit the accepted applicability of the results, and the study sheds light on combined teaching strategies focusing on active teaching-learning activities in the twenty-first century.